Introduction to Management - Mohanty, Sasmita; Pradhan, Bibhuti B (International Journal of Psychosocial Rehabilitation, 2019)
For human life management is the one of the most important activities. Managing has become essential to ensure the coordination of individual. Management refers to all types of organizations, including executives at all levels of the company. A principle of management are used not only for managing business but in all walks of life such as government, military, social and educational institutions etc. In all organisation management process is same. But with size and level of organisation, it may vary widely in its complexity. For every organisation management is the life giving element. Good management is the backbone of successful organizations. Managing life means getting things done to achieve life’s objectives and managing an organization means getting things done with and through other people to achieve its objectives. A set of principle related to management are planning, organizing, directing and controlling, and the application of these principles in harnessing physical, financial, human and informational resources efficiently and effectively to achieve organizational goals.